Influence of peripheral nerve system on proliferation and migration of keratinocytes on site of the wound edges - E. V. Artemova; Z. N. Dzhemilova; A. M. Gorbacheva; G. R. Galstyan; A. Yu. Tokmakova; A. B. Berdalin; S. A. Gavrilova (Сахарный диабет)
AIM: to assess proliferation and migration of keratinocytes at the nonhealing edges of neuropathic wounds.MATERIALS AND METHODS: 25 patients with neuropathic ulcers and 5 patients without diabetes with decubitus were enrolled. Diabetic foot (DF) patients were underwent to standard treatment including debridement, atraumatic dressing, offloading, antibacterial therapy if it needs. Severity of peripheral neuropathy was assessed according to the NDS scale. Histological (hematoxylin and eosin) and immunohistochemical (Ki-67 , α7nAChR markers) examination of wound edge were done during treatment (0, 10, 24 days).RESULTS: All patients have severe neuropathy according to NDSm (>8). The average size of DF ulcers before and on 10th day of treatment was of 4 cm2 and 2,5 cm2, respectively (p<0,004). Neuropathic ulcers were characterized by hyperproliferative epidermis. Mitotically active keratinocytes reside throughout the suprabasal layers. Ki-67 expressed all layers of the epidermis, but a greater staining density was detected in the basal layer. The density of a7nAChR-positive cells increased from 0 to 24 days (p=0,031).THE CONCLUSION: The data shows that neuropathy is one of the possible mechanisms of keratinocyte cell cycle disruption: proliferative activity and ability to migrate. Identification of new signaling pathways regulating the physiological repair of tissues and the study of their disorders in diabetes mellitus opens the prospect of developing an optimal therapeutic strategy.